The Integration of Artificial Intelligence and Its Impact on Managers’ Emotional Competencies: Toward a Redefinition of Leadership - KHATTABI , Ikram; EL AMILI , Omar; TAYEB , Dounia (Revue Internationale du Chercheur, 2025)
Abstract This article explores the impact of AI on emotional competencies and transformational leadership in managers within Moroccan SMEs. Through a conceptual model, we analyze how the integration of AI modifies managers’ emotional competencies and influences their ability to adopt transformational leadership. Using a confirmatory quantitative approach based on a representative sample of 71 SME managers, we highlight the mediating role of emotional competencies in the relationship between AI and transformational leadership. The results indicate that AI has a significant effect on the development of emotional competencies, which in turn facilitates the adoption of transformational leadership. This dynamic emerges as a key factor for SMEs in their adaptation process to contemporary technological challenges. The study suggests that considering emotional competencies in change management is essential for the success of SMEs in an increasingly digitized environment.